Tracking macaroni penguins during long foraging trips using ‘behavioural geolocation’ - Rory Wilson (Polar Biology, 2009)
Green, J. A., Wilson, R. P., Boyd, I. L., Woakes, A. J. Green, C. J., Butler, P. J. (2009). Tracking macaroni penguins during long foraging trips using ‘behavioural geolocation’. Polar Biol. 32; 645-653.